2015
DOI: 10.1073/pnas.1424626112
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular forms of IL-37 inhibit innate inflammation in vitro and in vivo but require the IL-1 family decoy receptor IL-1R8

Abstract: Similar to IL-1α and IL-33, IL-1 family member IL-37b translocates to the nucleus and is associated with suppression of innate and adaptive immunity. Here we demonstrate an extracellular function of the IL-37 precursor and a processed form. Recombinant IL-37 precursor reduced LPS-induced IL-6 by 50% (P < 0.001) in highly inflammatory human blood-derived M1 differentiated macrophages derived from selective subjects but not M2 macrophages. In contrast, a neutralizing monoclonal anti-IL-37 increased LPS-induced I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
243
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(263 citation statements)
references
References 28 publications
17
243
2
1
Order By: Relevance
“…Notably, the importance of IL-37 in modulating the inflammatory response is also supported by recent data showing that decreased IL-37 expression in patients with Behçet's disease triggers the Th17-inflammation response (29). Although the molecular mechanism of IL-37 in autoimmune disease remains unknown, recent studies showed that IL-37 acts as an extracellular cytokine by binding IL-18R and IL-1R8 for its anti-inflammatory properties (30). In addition, IL-37 fails to inhibit IL-17-triggering cytokine (IL-1b and IL-6) production and the MAPK signaling pathway in DCs from IL-1R8-deficient mice (30).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Notably, the importance of IL-37 in modulating the inflammatory response is also supported by recent data showing that decreased IL-37 expression in patients with Behçet's disease triggers the Th17-inflammation response (29). Although the molecular mechanism of IL-37 in autoimmune disease remains unknown, recent studies showed that IL-37 acts as an extracellular cytokine by binding IL-18R and IL-1R8 for its anti-inflammatory properties (30). In addition, IL-37 fails to inhibit IL-17-triggering cytokine (IL-1b and IL-6) production and the MAPK signaling pathway in DCs from IL-1R8-deficient mice (30).…”
Section: Discussionmentioning
confidence: 88%
“…Although the molecular mechanism of IL-37 in autoimmune disease remains unknown, recent studies showed that IL-37 acts as an extracellular cytokine by binding IL-18R and IL-1R8 for its anti-inflammatory properties (30). In addition, IL-37 fails to inhibit IL-17-triggering cytokine (IL-1b and IL-6) production and the MAPK signaling pathway in DCs from IL-1R8-deficient mice (30). A recent study showed that IL-17 expression was dramatically enhanced in IL-1R8-deficient mice (31).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SIGIRR has long been considered as an orphan receptor with unknown ligand molecules. Recently, human SIGIRR was found to act as a coreceptor with IL-18Ra for the recognition of IL-37, uncovering the existence of a previously unknown mechanism underlying the SIGIRR-mediated inflammatory regulation (3,53). Although well identified in mammals and predicted to be conserved from chicken to humans on the basis of sequence and expression patterns (54), the occurrence and existence of the SIGIRR homolog in lower vertebrates, including teleost fish, are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have demonstrated that such functions of IL-37 are mainly related to its inhibition of the release of inflammatory cytokines, including IL-1β, IL-18, and TNF-α (Li et al, 2015;Nold-Petry et al, 2015). For example, IL-37 can potentiate the inhibitory function of IL-18BP on IL-18 via specific binding (Bufler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%